2019
DOI: 10.1042/bsr20181614
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates acute kidney ischemia/reperfusion injury in diabetic rats by activation of the SIRT1/Nrf2/HO-1 signaling pathway

Abstract: Background and aims: Diabetic kidney is more sensitive to ischemia/reperfusion (I/R) injury, which is associated with increased oxidative stress and impaired nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling. Melatonin, a hormone that is secreted with the rhythm of the light/dark cycle, has antioxidative effects in reducing acute kidney injury (AKI). However, the molecular mechanism of melatonin protection against kidney I/R injury in the state of diabetes is still unknown. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 66 publications
(62 reference statements)
5
85
0
Order By: Relevance
“…Altogether, these results suggest that modulation of pro-oxidant and antioxidant enzymes by melatonin presumably contributes, at least in part, to its protective effect against AA-induced oxidative injury. In good agreement with our findings, melatonin has been shown to suppress oxidative stress and regulate pro-oxidant and antioxidant enzymes in animal models of AKI [8][9][10][11] and CKD [12][13][14]. Besides, the hormone is well known to have potent ROS-scavenging activity [3].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Altogether, these results suggest that modulation of pro-oxidant and antioxidant enzymes by melatonin presumably contributes, at least in part, to its protective effect against AA-induced oxidative injury. In good agreement with our findings, melatonin has been shown to suppress oxidative stress and regulate pro-oxidant and antioxidant enzymes in animal models of AKI [8][9][10][11] and CKD [12][13][14]. Besides, the hormone is well known to have potent ROS-scavenging activity [3].…”
Section: Discussionsupporting
confidence: 90%
“…Such effects of AA were effectively suppressed by melatonin. In line with our findings, melatonin has been shown to exert anti-apoptotic effects in animal models of AKI [6][7][8]. In order to obtain further mechanistic insights into the anti-apoptotic effects of melatonin, we performed Western blot analysis to assess protein levels of p53 in the kidneys, because p53 knockout mice were resistant to AA-induced apoptosis of tubular epithelial cells [29].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In a 4-week in vivo study, Shi et al evaluated the therapeutic effects of melatonin on renal I/R of diabetic rats. Animals were treated with or without melatonin, and renal I/R injury was induced by clamping right and left renal pedicles for 30 min followed by reperfusion for 48 h. Diabetic rats treated with melatonin were protected against renal injury, in aspects of oxidative stress and cell apoptosis in kidney [174].…”
Section: Melatonin Is An Appropriate Agent For the Treatment Of Diabementioning
confidence: 99%
“…evidence has accumulated supporting the fact that dM aggravates renal i/r injury (5). experimental studies have revealed that diabetic rats develop renal dysfunction faster following ir injury compared with non-diabetic rats (6,7). other research has revealed that progressive hyperglycemia can cause increased levels of reactive oxygen species (roS) in the diabetic kidney following i/r injury (8).…”
Section: Introductionmentioning
confidence: 99%